Effects of situational variables on offensive performance indicators in elite water polo - Garcia-Ordóñez, E.; Tourino Gonzalez, C.; del Carmen Iglesias-Pérez, M. (International Journal of Performance Analysis in Sport, 2017)
The aim of this study was to assess the effect of quality of opposition, starting quarter score and match location on offensive performance indicators in the First Spanish Professional Water Polo League. Eighty-eight matches from the 2011-2014 domestic league seasons were notated post-event using a computerised notational analysis system. The dependent variables were team offensive performance indicators, and the independent variables were situational variables (quality of opposition, starting quarter score and match location). Univariate analyses (ANOVA test; Student`s t-test, Kruskal-Wallis test, Mann-Whitney U test and Generalized Linear Model test) indicated that "Even attacks", "Counterattacks", "Goals", "No goal shots", "Even shots", "Counterattack shots", "Shots zone 4, 5, and 6", "Drive shots" and "Shots after 2 flakes", were influenced by a least one of the three situational variables. Two-way ANOVA analyses were applied in order to study, not only the main effects of the situational variables on "Counterattacks" and "Goals", but also the interaction effect. Although the interaction effects were not significant, the adjusted effects of the situational variables were obtained and the findings emphasise the need for match analysts and coaches to consider single and adjusted potential effects of quality of opposition, starting quarter score and match location, during assessments of the offensive performance indicators of water polo performance.